The Vow-Curse in Ancient Jewish Texts - Bamberger, Avigail Manekin (Harvard theological review, 2019)
Uttering a vow was an important and popular religious practice in ancient Judaism. It is mentioned frequently in biblical literature, and an entire rabbinic tractate, Nedarim, is devoted to this subject. In this article, I argue that starting from the Second Temple period, alongside the regular use of the vow, vows were also used as an aggressive binding mechanism in interpersonal situations. This practice became so popular that in certain contexts the vow became synonymous with the curse, as in a number of ossuaries in Jerusalem and in the later Aramaic incantation bowls. Moreover, this semantic expansion was not an isolated Jewish phenomenon but echoed both the use of the anathema in the Pauline epistles and contemporary Greco-Roman and Babylonian magical practices.